1993
DOI: 10.1002/cjce.5450710107
|View full text |Cite
|
Sign up to set email alerts
|

The mean flow field produced by a 45° pitched blade turbine: Changes in the circulation pattern due to off bottom clearance

Abstract: The impeller discharge stream and bulk circulation flow produced by a pitched blade turbine (PBT) in a fully baffled stirred tank have been defined, using a combination of flow visualization and laser Doppler anemonietry measurement techniques. Two distinct bulk circulation patterns have been identified, one for higher off bottom clearances, and one for lower clearances. The circulation patterns are shown to have a substantial impact on the discharge stream, even very close to the edge of the impeller blades. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
70
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(90 citation statements)
references
References 19 publications
(13 reference statements)
16
70
1
1
Order By: Relevance
“…Investigations of [6] and [7] used 2-D and 3-D PIV techniques in mixing vessels stirred with 45°pitched blade and Rushton impellers, respectively, to estimate the turbulent dissipation rate and made comparison with previous estimated values made from single-point velocity measurement techniques. In particular, the former investigation showed that for a coarse spatial resolution of 5 mm the estimated rate of dissipation agrees well with that of the dimensional analysis employed by [5]. The latter study showed the feasibility of direct measurement of the dissipation distribution using both 2-D and 3-D PIV methods by measuring the mean velocities and Reynolds stresses simultaneously from which the dissipation rate was determined.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Investigations of [6] and [7] used 2-D and 3-D PIV techniques in mixing vessels stirred with 45°pitched blade and Rushton impellers, respectively, to estimate the turbulent dissipation rate and made comparison with previous estimated values made from single-point velocity measurement techniques. In particular, the former investigation showed that for a coarse spatial resolution of 5 mm the estimated rate of dissipation agrees well with that of the dimensional analysis employed by [5]. The latter study showed the feasibility of direct measurement of the dissipation distribution using both 2-D and 3-D PIV methods by measuring the mean velocities and Reynolds stresses simultaneously from which the dissipation rate was determined.…”
Section: Introductionsupporting
confidence: 63%
“…The results of [3] were more detailed and revealed that the velocities scaled with rotational speed and that the hydraulic efficiency increases with the blade pitch. The studies of [4][5] also used 45°pitched-blade impellers and showed the bulk flow patterns are different for low and high off-bottom clearances. Detailed time-resolved LDV measurements by [1] for a 60°pitched blade impeller revealed an axial jet which originated beneath the impeller and formed a large ring vortex covering up to two thirds of the vessel height, a small vortex was shed from the tip of each blade which decayed rapidly, a swirl velocity beneath the impeller proportional to radius and that the turbulence in the discharge region was in general anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…For the higher clearance the impeller stream turned upwards before reaching the base of the vessel, generating also a reverse flow directed radially from the walls towards the vessel axis at the base of the vessel. Kresta & Wood (1993) measured the mean flow field of a vessel stirred with a 4-bladed 45° PBT for two impeller sizes, i.e. D = T/3 and D = T/2, and varying the impeller clearance systematically from T/20 up to T/2.…”
Section: Classification Of Flow Instabilitiesmentioning
confidence: 99%
“…The existence of MI has been confirmed by various experimental methods (e.g. Kresta & Wood 1993;Brůha et al 1996;Montes et al 1997;Bittorf & Kresta 2000;Nikiforaki et al 2003). The presence of the MI in the flow pattern is displayed by distinct peaks in the low-frequency part of the power spectrum of a signal measured in the tank.…”
Section: Introductionmentioning
confidence: 76%
“…This difference arises from the different structure and properties of fluid streams in these two regions (e.g. Kresta & Wood 1993). Figures 3 and 4 give more detailed views of the spatial distributions of the l max and d c values over the grid of the experimental points.…”
Section: Resultsmentioning
confidence: 99%